2021
DOI: 10.3390/ijms22031471
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor-Based Directed Evolution of Methanol Dehydrogenase from Lysinibacillus xylanilyticus

Abstract: Methanol dehydrogenase (Mdh), is a crucial enzyme for utilizing methane and methanol as carbon and energy sources in methylotrophy and synthetic methylotrophy. Engineering of Mdh, especially NAD-dependent Mdh, has thus been actively investigated to enhance methanol conversion. However, its poor catalytic activity and low methanol affinity limit its wider application. In this study, we applied a transcriptional factor-based biosensor for the direct evolution of Mdh from Lysinibacillus xylanilyticus (Lxmdh), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
(17 reference statements)
0
26
0
Order By: Relevance
“…Despite extensive use of ligand-dependent biosensors for detecting small molecules in cells [65][66][67] , their use in assays for directed evolution is rare [68][69][70] , and only one example of their use for continuous evolution systems has been reported 34 . In this study, we engineered multiple biosensors to detect diverse small molecule ligands and yield pIII or a reporter gene as an output.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive use of ligand-dependent biosensors for detecting small molecules in cells [65][66][67] , their use in assays for directed evolution is rare [68][69][70] , and only one example of their use for continuous evolution systems has been reported 34 . In this study, we engineered multiple biosensors to detect diverse small molecule ligands and yield pIII or a reporter gene as an output.…”
Section: Discussionmentioning
confidence: 99%
“…(such as C. necator (Wu et al, 2016)). In particular, their NAD +dependent Mdhs have been focused and reported for studies of recombinant E. coli as synthetic methylotrophs (Müller et al, 2015;Wu et al, 2016;Whitaker et al, 2017;Lee et al, 2020;Le et al, 2021). Three NAD + -dependent Mdhs have been found in B. methanolicus MGA3 (Mdh, Mdh2, and Mdh3).…”
Section: Nad + -Dependent Mdhmentioning
confidence: 99%
“…In vitro studies suggest that ACT enhances the methanol affinity, oxidation rate, and catalytic activity of Mdhs; however, the detailed mechanism for activation is currently unclear (Hektor et al, 2002;Witthoff et al, 2015) and no effect has been shown in vivo in a synthetic methylotrophy (Müller et al, 2015) because detail research for the activator protein functions in native host has not been tested. To enable the assimilation of methanol as the carbon source in metabolic engineering, ACT-independent Mdhs and their mutants from C. necator (Wu et al, 2016;Chen et al, 2018) and L. xylanilyticus (Lee et al, 2020;Le et al, 2021) have been reported and introduced into E. coli for methanol assimilation. As best candidate for synthetic methylotrophy, NAD + -dependent Mdh that can perform its function under both aerobic and anaerobic conditions (Zhang et al, 2017).…”
Section: Nad + -Dependent Mdhmentioning
confidence: 99%
See 2 more Smart Citations